Jetting and migration of a laser-induced cavitation bubble in a rectangular channel. (10th October 2022) - Brujan, Emil-Alexandru; Zhang, A.-M.; Liu, Yun-Long; Ogasawara, Toshiyuki; Takahira, Hiroyuki
Abstract: Abstract : The jetting behaviour and migratory characteristics of a laser-induced cavitation bubble in a rectangular channel are investigated both experimentally and numerically, for various combinations of the geometric and physical parameters of the system. High-speed photography is used to visualize the temporal development of the bubble shape, the formation of liquid jets during bubble collapse, and the bubble displacement in contact with the sidewalls of the channel during two oscillation cycles of the bubble. The bubble profiles, pressure contours and velocity vectors ambient to the bubble are obtained through numerical simulation results by using an Eulerian finite element method with a compressible liquid impact model. The jetting behaviour of the bubble varies between single jet formation and the formation of three liquid jets directed towards each wall of the channel. The numerical calculations indicate that the liquid jets directed towards the sidewalls of the channel reach maximum velocities of 100 m s −1 while the peak velocity of the liquid jet directed towards the channel endwall is about 55 m s −1 . A small bubble generated close to a sidewall of the channel develops only a single inclined jet during collapse. Such jets can reach velocities of up to 110 m s −1 . A bubble displacement in contact with the sidewalls of the channels of 350 μm was observed during the first two oscillation cycles for a bubble with a maximum diameter slightly smaller than the height of the channel. The results of our investigations are compared to previous results obtained in similar configurations.